KESANTUNAN BERBAHASA DALAM TINDAK TUTUR YANG BERORIENTASI PADA KEARIFAN LOKAL ANTARA BANTEN DAN MINANGKABAU SEBAGAI PENDIDIKAN KARAKTER - Ediwarman Ediwarman (Universitas Sultan Ageng Tirtayasa, 2016)
The importance of culture and character education for rationale, attitudes, and behaviors of learners leaving from education values, morals, manners, and character given by teachers who notabennya as educators. An educator said to be in character if he has values and beliefs are based on the nature and purpose of education, as well as used as a moral force in their duties as educators. Politeness speech acts of teachers in character education has values that are very important to understand how the ethics or morality of a teacher interact in the learning process. Polite language is the most appropriate tool used in communication. The students need to be nurtured and directed to speak politely, because students are the future generation that will live up to its time. If a protege left no mannered speaking it is not impossible that already while the polite language can be lost and the next generation is born arrogant, rough, dry on the values of ethics, religion and character. The key values that characterize the teacher in the act says that manners are tolerance, exemplary, maximum services, emotional and intellectual as well as the importance of the transformation of the value of local cultural traditions or local knowledge through education is perceived important by author and teacher Indonesian particularly in politeness.